Breastfeeding associated with higher lung function in African American youths with asthma. (14th September 2017) - Oh, Sam S.; Du, Randal; Zeiger, Andrew M.; McGarry, Meghan E.; Hu, Donglei; Thakur, Neeta; Pino-Yanes, Maria; Galanter, Joshua M.; Eng, Celeste; Nishimura, Katherine Keiko; Huntsman, Scott; Farber, Harold J.; et al.
ABSTRACT: Objective: In the United States, Puerto Ricans and African Americans have lower prevalence of breastfeeding and worse clinical outcomes for asthma compared with other racial/ethnic groups. We hypothesize that the history of breastfeeding is associated with increased forced expiratory volume in 1 second (FEV1 ) % predicted and reduced asthma exacerbations in Latino and African American youths with asthma. Methods: As part of the Genes-environments & Admixture in Latino Americans (GALA II) Study and the Study of African Americans, asthma, Genes & Environments (SAGE II), we conducted case-only analyses in children and adolescents aged 8–21 years with asthma from four different racial/ethnic groups: African Americans ( n = 426), Mexican Americans ( n = 424), mixed/other Latinos ( n = 255), and Puerto Ricans ( n = 629). We investigated the association between any breastfeeding in infancy and FEV 1 % predicted using multivariable linear regression; Poisson regression was used to determine the association between breastfeeding and asthma exacerbations. Results: Prevalence of breastfeeding was lower in African Americans (59.4%) and Puerto Ricans (54.9%) compared to Mexican Americans (76.2%) and mixed/other Latinos (66.9%; p < 0.001). After adjusting for covariates, breastfeeding was associated with a 3.58% point increase in FEV1 % predicted ( p = 0.01) and a 21% reduction in asthma exacerbations ( p = 0.03) in African Americans only. Conclusion: Breastfeeding was associated with higher FEV1 % predicted in asthma and reduced number of asthma exacerbations in African American youths, calling attention to continued support for breastfeeding.